2023
DOI: 10.1037/law0000396
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-based evidence disclosure: Providing an operational purpose for disclosing evidence in investigative interviews.

Simon Oleszkiewicz,
Marika Madfors,
Matthew Jones
et al.

Abstract: Studying evidence disclosure methods in laboratory-based settings provides important contributions to evidence-based interview practices. However, methods developed through controlled testing need to be adapted to an operational context to ensure appropriate use in practice. The present project synthesized laboratory research on evidence disclosure and practical experience of homicide and robbery investigations to identify an operational purpose for disclosing evidence in investigative interviews. That purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For example, Alison et al (2013) showed that rapport-building techniques were associated with positive interview outcomes, while Place and Meloy (2018) found that rapport strategies involving empathy best overcame interviewee resistance. More recent studies emphasize that supportive interviewing promotes rapport, cooperation, and informativeness on the part of adult suspects (e.g., Dianiska et al, 2021;Oleszkiewicz et al, 2023;Vallano et al, 2022). Interestingly, a concern with rapport throughout the interview is more effective than a focus on rapport-building only early in the interview (Baker-Eck & Bull, 2022).…”
Section: Rapport and Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Alison et al (2013) showed that rapport-building techniques were associated with positive interview outcomes, while Place and Meloy (2018) found that rapport strategies involving empathy best overcame interviewee resistance. More recent studies emphasize that supportive interviewing promotes rapport, cooperation, and informativeness on the part of adult suspects (e.g., Dianiska et al, 2021;Oleszkiewicz et al, 2023;Vallano et al, 2022). Interestingly, a concern with rapport throughout the interview is more effective than a focus on rapport-building only early in the interview (Baker-Eck & Bull, 2022).…”
Section: Rapport and Supportmentioning
confidence: 99%
“…Using the RSP, interviewers fostered greater responsiveness during the rapport-building phase, providing more details about a neutral event and sharing more information about themselves, suggesting that the children were more comfortable, trusting, and cooperative (Dianiska et al, 2021;Oleszkiewicz et al, 2023;Vallano et al, 2022). Similarly, the RP better promoted rapport during interviews with young suspected victims although interviewers tend to be more suspicious of young suspects than of alleged victims (Malloy & Lamb, 2010) and therefore rapport building with suspects is probably more challenging.…”
Section: Rapport Building and Maintenancementioning
confidence: 99%